2017
DOI: 10.1016/j.atmosenv.2016.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Radiation fog chemical composition and its temporal trend over an eight year period

Abstract: Radiation fog samples have been collected at a rural site in Central Pennsylvania from 2007 through 2015 in order to document chemical composition, assess concentration changes over time, and to provide insight into emission sources that influence the region. The collection of samples over multiple years makes this one of the few long duration radiation fog studies that have been completed.During the course of the campaign, 146 samples were obtained and analyzed for pH, major inorganic ions, low molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 91 publications
2
4
0
Order By: Relevance
“…Four categories of samples with different air mass history characteristics were compared, revealing a few notable features: (i) while speciated concentrations and TOC masses varied considerably between the four cases, the contributions of MCAs and DCAs (based on C mass) to TOC were remarkably similar with little variation (MCA : TOC = 16.03 %-23.66 % and DCA : TOC = 3.70 %-8.75 %); (ii) dust and sea salt tracer species were strongly correlated with most of the speciated organics for the North and East cases, suggestive of interactions between such species and coarse aerosol surfaces, as supported by past work (Stahl et al, 2020;Sullivan and Prather, 2007); (iii) for samples with limited aging (North case) based on selected chemical ratio values, adipate was more abundant and was negatively correlated with smaller carboxylic acids; (iv) BB samples exhibited the highest TOC concentrations (8342 ± 3730 ppb C) as well as significantly elevated levels of individual organics such as acetate, formate, succinate, glutarate, pyruvate, oxalate, and MSA; and (v) the Clark case had a higher variability in TOC (1181 ± 920.2 ppb C) than the North and East cases, presumably owing to a greater mix of influential sources such as fresh anthropogenic emissions (e.g., enhanced maleate) as well as the transport of biomass burning plumes from Borneo and Sumatra (e.g., enhanced succinate), dust, and spatial and temporal variances across different flights. Related to dust, Ca 2+ was only correlated with adipate in the Clark samples, which is consistent with a recent study in Metro Manila (Stahl et al, 2020) showing that adipate uniquely exhibits a prominent supermicrometer peak among organic acids, attributed to interactions with dust.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Four categories of samples with different air mass history characteristics were compared, revealing a few notable features: (i) while speciated concentrations and TOC masses varied considerably between the four cases, the contributions of MCAs and DCAs (based on C mass) to TOC were remarkably similar with little variation (MCA : TOC = 16.03 %-23.66 % and DCA : TOC = 3.70 %-8.75 %); (ii) dust and sea salt tracer species were strongly correlated with most of the speciated organics for the North and East cases, suggestive of interactions between such species and coarse aerosol surfaces, as supported by past work (Stahl et al, 2020;Sullivan and Prather, 2007); (iii) for samples with limited aging (North case) based on selected chemical ratio values, adipate was more abundant and was negatively correlated with smaller carboxylic acids; (iv) BB samples exhibited the highest TOC concentrations (8342 ± 3730 ppb C) as well as significantly elevated levels of individual organics such as acetate, formate, succinate, glutarate, pyruvate, oxalate, and MSA; and (v) the Clark case had a higher variability in TOC (1181 ± 920.2 ppb C) than the North and East cases, presumably owing to a greater mix of influential sources such as fresh anthropogenic emissions (e.g., enhanced maleate) as well as the transport of biomass burning plumes from Borneo and Sumatra (e.g., enhanced succinate), dust, and spatial and temporal variances across different flights. Related to dust, Ca 2+ was only correlated with adipate in the Clark samples, which is consistent with a recent study in Metro Manila (Stahl et al, 2020) showing that adipate uniquely exhibits a prominent supermicrometer peak among organic acids, attributed to interactions with dust.…”
Section: Discussionsupporting
confidence: 69%
“…Wang et al (2018) showed that East Asian dust can get lofted up during dust storms, which could contribute to the transport to the Philippines. Previous studies have shown that organic acids adsorb more readily to dust compared with sea salt due to dust's more alkaline nature (Stahl et al, 2020;Sullivan and Prather, 2007). While Ca 2+ was correlated with 6 of the 11 organic species for this case (r = 0.70-0.96; Table S2), the magnitude of the correlations was very similar to those between either Na + or Cl − and the speciated organics.…”
Section: Eastmentioning
confidence: 49%
See 1 more Smart Citation
“…Importantly, these are only estimates of HCO − 3 concentrations based on equilibrium with the atmosphere. There has been significant discussion on the validity of Henry's Law constants for cloud drop distributions, as several field studies note significant departures of measurements from gasaqueous phase partitioning (Pandis and Seinfeld, 1991;Winiwarter et al, 1994;Straub, 2017). It is plausible that some deviations could also exist for the carbonate system, thus leading to inaccurate HCO − 3 concentration estimates.…”
Section: Bicarbonatementioning
confidence: 99%
“…Routine long-term measurements of cloud water or fog water are not widely available, but other locations worldwide have seen similar long-term reductions in SO 2− 4 and/or NO − 3 concentrations with concomitant decrease in acidity, including California's central valley (Herckes et al, 2015), Pennsylvania (Straub, 2017), New Hampshire (Murray et al, 2013), the UK (Cape et al, 2015), Italy (Giulianelli et al, 2014), France (Deguillaume et al, 2014) and Japan (Yamaguchi et al, 2015;Watanabe et al, 2022). A thorough review of both long-term and short-term cloud and fog chemistry studies has been recently compiled by Isil et al (2022).…”
Section: Introductionmentioning
confidence: 99%